The Effects of Multinational Production on Workers’ Wages and Working Conditions in Cavite Economic Zone - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
Workers are a building block for every corporate development-domestic or foreign.  The introduction of multinationals in the Phillipines has so long been historic in its economic development.  The turn of the 21 st has brought the Phillipines new economic challenges, and on how it has propelled its economic amid the implacable financial crisis.  Yet the presence of economic zones in the country, particularly the Cavite Economic Zone (CEZ), has helped the nation resurface into an economic breath from among other Asean economies.  Together with other specialized zone on the country, CEZ has a great role in the economic development platform of the government, yet its infrastructures have been replete with issues on substandards attention toward workers’ welfare.  This study sought to determine the effects of multinational productions on workers’ wages and working conditions in Cavite Economic Zone.  How this people are being compensated and treated in their working environment has undoubtedly great impact in their daily family and working lives in the company they each represent.